Innovations and implementations of clustered regularly interspaced short palindromic repeats in next-generation diagnostic tools: A review of current and emerging techniques - Samudrala Lahari; Y. Sneha; Chitti Sathwika; Meghavath Tharun; T. Rama Rao (Journal of Clinical Sciences)
Introduction: The development of CRISPR technology has ushered in a new era in molecular diagnostics whereby genetic material can be very accurately and efficiently detected. Therefore, the incorporation of these technologies into diagnostic protocols represents a paradigm shift in precision medicine. This review aims to thoroughly assess the advancements and application of CRISPR into next-generation diagnostic tools, focusing on both existing and emerging technologies. Methods: The review presents CRISPR-based systems as historically moving from simple genome-editing tools into advanced diagnostic platforms, with emphasis on utilities that enhance diagnostic capability such as field-deployable assays and multiplex detection methodologies. Results: The review discusses CRISPRs-Cas13 and Cas12-and-Cas9 systems and their applications in the detection of infectious diseases, genetic disorders, and cancer. Emerging Techniques: The article points out emerging techniques using CRISPR for real-time monitoring and point-of-care diagnostics, showcasing the technology’s transformational capacity in diagnostic practice across various fields. Challenges and opportunities: The review outlines challenges and opportunities for CRISPR diagnostics, which include artificial intelligence configuration, multiplexing capability, and possibilities for personalized medicine. Conclusion: This review aims at highlighting the disrupting powers of CRISPR technologies on diagnostic systems toward the development of accurate, accessible, and inexpensive solutions for diagnostics in precision health.